Investigation of treatment process and treatment sufficiency of marble mine wastewater: a case study in Turkey - Dede, Omer Hulusi; Dede, Cemile; Sakar, Sueleyman; Sazak, Mueserref; Ozer, Hasan (SPRINGER, 2020)
In this study, wastewater formed in marble mines operated as open mines with the aid of a cutting slope in the soil clarification tanks, which were made impermeable by using membranes and similar impermeable elements, was collected after the sedimentation process. The reusability of the water during the process was also investigated. In the marble mines where the study was carried out, an average of 25 m(3)/day of water is used as the process water for cutting operations. It is thought that similar to 10 m(3)/day of this water is evaporated or remains between the marble blocks. However, in the facility, 15 m(3)/day of wastewater was collected in the clarification tank that was made impermeable with a plastic cover. The initial (I) and final (F) values for the suspended solid (SS), pH, colour (C), oil and grease (OG) and Cr6+ were determined as SSI = 106.5 mg/l, SSF = 58.3 mg/l, pH(I) = 8.06, pH(F) = 7.93, C-I = 83.5 (Pt-Co), C-F = 47.5 (Pt-Co), (Cr6+)(I) = < 0.05 mg/l, (Cr6+)(F) = < 0.05 mg/l, OG(I) = 8.7 mg/l and OG(F) = 2.3 mg/l. The fact that these values are below the required limits in the Water Pollution Control Regulation applied in Turkey indicates that the treatment is successful and that the clarification tank is working effectively. Therefore, this method can be used successfully in marble mines.
Keywords: Wastewater treatment; Marble mine; Treatment sufficiency; Treatment process; REMOVAL; Science & Technology - Other Topics; Environmental Sciences & Ecology